2014
DOI: 10.7150/ijms.8383
|View full text |Cite
|
Sign up to set email alerts
|

Activated Hair Follicle Stem Cells and Wnt/β-catenin Signaling Involve in Pathnogenesis of Sebaceous Neoplasms

Abstract: Sebaceous glands (SGs) undergo cyclic renewal independent of hair follicle stem cells (HFSCs) activation while HFSCs have the potential to differentiate into sebaceous gland cells, hair follicle and epidermal keratinocytes. Abnormalities of sebaceous gland progenitor cells contribute to the development of sebaceous neoplasms, but little is known about the role of HFSCs during sebaceous neoplasm development. Here, using dimethylbenzanthracene (DMBA) plus 12-o-tetradecanoyl phorbol-13-acetate (TPA) treatment dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Wnt signaling usually maintains at a low level which is under the threshold for hair follicle stem cell activation at telogen [ 29 ]. Overexpression of β-catenin in epidermis induces ectopic hair follicle regeneration [ 30 ], and even tumorigenesis [ 31 ]. In our study, we found β-catenin expression is increased in telogen skin of aged mice compared to those in young mice.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling usually maintains at a low level which is under the threshold for hair follicle stem cell activation at telogen [ 29 ]. Overexpression of β-catenin in epidermis induces ectopic hair follicle regeneration [ 30 ], and even tumorigenesis [ 31 ]. In our study, we found β-catenin expression is increased in telogen skin of aged mice compared to those in young mice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hair follicle tumors were observed to have stable expression of β-catenin in mice (Gat et al, 1998). A recent study found hair follicle stem cells (HFSC) treated with dimethylbenzanthracene (DMBA) and 12- O -Tetradecanoylphorbol-13-acetate (TPA) induced sebaceous neoplasms in C57BL/6 mice, as well as increased Wnt10b expression in basal cells via immunostaining (Qiu et al, 2014). Here the authors propose a model wherein increased Wnt10b results in proliferation and differentiation of HFSCs and thus promoting sebaceous neoplasms.…”
Section: Introductionmentioning
confidence: 99%
“…Other neoplasms of skin appendages, such as neoplasms of eccrine or sebaceous glands, have only been examined in a few cases. Human sebaceous neoplasms, especially sebaceoma, and also sebaceous carcinomas, have been reported to express CK15, SOX9 and β‐catenin, as have mouse models of sebaceous neoplasms . CK15, CK19, carcinoembryonic antigen, CAM5·2 and nestin have been reported to stain poroma and porocarcinoma to enable distinction from SCCs …”
Section: Discussionmentioning
confidence: 99%
“…Human sebaceous neoplasms, especially sebaceoma, and also sebaceous carcinomas, have been reported to express CK15, SOX9 and b-catenin, 25,30,41 as have mouse models of sebaceous neoplasms. 41,42 CK15, CK19, carcinoembryonic antigen, CAM5Á2 and nestin have been reported to stain poroma and porocarcinoma to enable distinction from SCCs. 43,44 We used markers that had been previously reported, such as CK15, b-catenin and SOX9, together with hair follicle stem cell markers that have not been previously reported, such as Lgr5 [except for the detection of Lgr5 (GPR49) mRNA in BCCs] 45 and Lrig1, but that label different areas of the hair follicle to enact a cell origin profile in skin appendage malignancies.…”
Section: Discussionmentioning
confidence: 99%